Who Can Lie to a Robot? Roboethics and Categorical Imperative - Quintanilla Navarro, Ignacio (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2014)
This paper analyzes the impact of our new technological system in the evolution and structure of our ethical argumentation.Considering the possibility of the deception in the relationship human-robot, the paper discusses some of the implications of the ethical doctrines of Kant and Scheler in a situation of human-robot communication. After a historical analysis of the relationship between technology and ethical argumentation the paper proposes an interpretation of the moral argument exposed by Kant in his essay “On a Supposed Right to Lie Because of Philanthropic Concerns”, published in 1979, in the context of the interaction human being-robot. The final section offers some suggestions on general roboethics.